Values-Based Organizational Resilience: A Qur’an-Informed Multi-Level Framework Integrating Leadership, Ethics, and Employee Behavioral Mechanisms (Al-Qamar, 2025)
This study develops an integrative Qur’an-informed model of organizational resilience by systematically aligning leadership and employee instructions derived from primary Qur’anic verses with contemporary theories in strategic management, leadership, and human resource management. Drawing on stewardship theory, ethical and transformational leadership, organizational justice, social learning, and the resource-based view, the model conceptualizes resilience as a multilevel outcome emerging from prudent financial governance, humane people management, exemplary role modeling, emotional regulation, and disciplined performance. At the leadership level, practices such as financial stewardship, due care, ethical workforce separation, patience, and equitable treatment cultivate trust, psychological safety, and adaptive capacity. At the employee level, commitment, humility, emotional self-regulation, learning from errors, and consistent high performance function as behavioral mechanisms that reinforce individual and collective resilience. By bridging Qur’anic primary sources with established management theories, this study advances a novel, values-based framework that extends resilience scholarship beyond conventional secular models and offers a theoretically grounded, ethically robust, and practically actionable approach to sustaining organizational performance and competitive advantage under conditions of uncertainty.
Keywords: Organizational Resilience; Ethical Leadership; Stewardship Theory; Qur’anic Management Framework; Strategic Leadership